Ultrastructural observations on the beneficial effects of polyunsaturated fatty acids (EPA and HDA) (Omega-3) on the aortic wall in cholesterol-fed rabbits - (:unkn) unknown (Thieme Medical Publishers, Inc., 1997)
The effects of a cholesterol-rich diet and linolenate-derived polyunsaturated fatty acids (Omega-3; EPA and HDA) supplementation on the aortic ultrastructure and serum lipid profiles (total cholesterol, HDL- cholesterol, and LDL-cholesterol) were investigated in rabbits. Three groups were established as follows: Group 1 (control) rabbits received regular diet (n = 8), Group 2 received regular diet enriched with cholesterol for 12 months (n = 14), and Group 3 received regular diet enriched with cholesterol for 4 months, then replaced by Max-EPA supplementation in the remaining 8 months (n = 14). Crater-like openings on the endothelial cells and the presence of lipid vacuoles in cholesterol-fed rabbits (Group 2) suggest a very rapid uptake of circulating plasma lipids from the aortic lumen. In Group 3, the ultrastructure of the endothelial cells was almost normal and no lipid vacuoles were noted. Lipids stored in the subendothelial and adventitial regions of the vessel were noted. Biochemical findings were in accordance with the ultrastructural findings in Groups 2 and 3. It is possible that, in the cholesterol-fed, EPA, and HDA-replaced rabbits, endothelial cells may stop or reduce lipid uptake from the lumen and/or the rate of transport of lipid particles may increase. In other words, the behavior of the endothelial cells might be altered by the polyunsaturated fatty acids, as well as their circulating lipid-lowering action.